Impact of salbutamol on muscle metabolism assessed by 31P NMR spectroscopy. Issue 3 (17th September 2014) - Decorte, N.; Lamalle, L.; Carlier, P.G.; Giacomini, E.; Guinot, M.; Levy, P.; Verges, S.; Wuyam, B.
<x xml:space="preserve">Abstract</x> The potential ergogenic effects of oral salbutamol intake were demonstrated for decades but the underlying mechanisms remain to elucidate. We hypothesized that improved exercise performance after acute oral salbutamol administration is associated with changes in muscle metabolism. Twelve healthy, nonasthmatic, moderately trained, male subjects were recruited to compare in a double‐blind crossover randomized study, an oral dose of salbutamol (4 mg) and a placebo. After treatment administration, subjects performed repetitive plantar flexions to exhaustion in a 3T magnet. Continuous 31P nuclear magnetic resonance spectroscopy assessment of the calf muscles was performed at rest, during exercise, and during recovery. No significant difference between treatments was detected in metabolite concentration at rest (P > 0.05). Creatine phosphate and inorganic phosphate changes during and immediately after exercise were similar between treatments (P > 0.05). Intramuscular pH (pHi) was significantly higher at rest, at submaximal exercise but not at exhaustion with salbutamol (pHi at 50% of exercise duration, 6.8 ± 0.1/6.9 ± 0.1 for placebo and salbutamol, respectively, P < 0.05). The maximal power (28 ± 7 W/23 ± 7 W; P = 0.001) and total work (1702 ± 442 J/1381 ± 432 J; P = 0.003) performed during plantar flexions were significantly increased with salbutamol. Salbutamol induced significant improvement in calf muscle endurance with similar metabolic responses during exercise, except slight differences in pHi. Other mechanisms than changes in muscle metabolism may be responsible for the ergogenic effect of salbutamol administration.